The Nature of Supply Chain Management Research - Wolf, Julia (Springer, 2017)
The term Supply Chain Management (SCM) first occurred during the 1980s and has since experienced increasing attention from both theory and practice. Julia Wolf focuses on the theoretical aspect of SCM by analyzing the evolution SCM research has undergone and by assessing the question whether SCM research can be considered a scientific paradigm as of today. A number of factors are investigated based on empirical data gathered from publications on SCM in international refereed journals from 1990 to 2006. As a result, four major periods are distinguished in the evolution of SCM research: emergence, acceptance, growth and a final phase of establishment. These periods are characterized in terms of the following factors and their alterations over time: scientific values, object of study, constructs, methods, schools of thought, and the link of research to practice.